Pelatihan Storytelling Dapat Meningkatkan Speaking Skills dan Literasi Siswa - Afriana, Afriana; Oktavia, Yunisa; Husda, Nur Elfi; Hairi, Muhammad Imam Akbar (ASOSIASI IDEBAHASA KEPRI, 2024)
Storytelling is the scope of public speaking which concerns the way and art of speaking to other people or the public/audience. Therefore, telling stories requires repeated practice so that the speaker is confident and able to control himself and his audience. There are several things included in storytelling, namely MC/Host, Speech, Rhetoric, and so on. In conveying storytelling in public, you need skills in speaking and also literacy. Therefore, it is very important for speakers to master the material and stage by carrying out various kinds of training to develop literacy and grow self-confidence. To become a good speaker, you need to practice these two things. With storytelling training, speaking skills and literacy can be improved, especially for students in Batam, Riau Islands. This service looks at storytelling in improving students' speaking and literacy skills, exploring issues related to language learning and improving education. The design used is a qualitative research method. Data is collected through students' speaking and writing skills, as well as surveys and interviews with educators and students. In addition, community service activities are held to overcome barriers to language learning. Results showed that students who participated in storytelling activities showed significant improvements in speaking fluency, vocabulary use, and ability to compose detailed and clear literary descriptions.